Antecedents enabling team ambidexterity: moving beyond mere microfoundation. Issue 6 (21st October 2021) - Dean, Benjamin P.
Abstract : Purpose: Ambidexterity in teams represents powerful dynamic capabilities for innovation and adaptation in rapidly changing environments. This study focused on the emerging concept of team ambidexterity. Primary purposes were to consolidate emerging research on ambidexterity within teams and to synthesise antecedent inputs. Design/methodology/approach: This study applied a systematic content-based review method to collect articles relevant to enabling ambidexterity within teams. The study integrated relevant studies on ambidexterity and on teams and teamwork. It analysed content through theoretical frameworks of ambidexterity and dynamic capabilities. Findings: Team ambidexterity constitutes a distinct and increasingly important organisational concept beyond just supporting firm-level ambidexterity. Team ambidexterity depends on inputs that can include ambidexterity's multilevel, generic mechanisms and additional team-centric inputs specially characterising teams. Practical implications: Organisational leaders need insights into the valuable potential of ambidextrous teams that can increase innovation and enable successful adaptation at an operational level for longterm survival and competitive advantage in volatile environments. The study highlights the essential inputs for designing and equipping ambidextrous teams. Originality/value: Team ambidexterity research is growing, but so far it has mostly addressed team ambidexterity as a microfoundation supporting firm-level ambidexterity. Existing studies have remained mostly disparate and unorganized. This study appears unique in having identified and synthesised studies most relevant to developing ambidexterity within teams. The study articulated a more comprehensive understanding of team ambidexterity, derived a novel set of team-centric inputs and analysed ambidexterity as dynamic capabilities at operational unit level.